Pemanfaatan Sistem Monitoring Berbasis IoT Dan Sensor Cerdas Untuk Restorasi Ekosistem - Sri Hartanto (JURNAL ELEKTRO, 2026)
Indonesia has targeted a 31.89% reduction in greenhouse gas emissions through its own efforts and up to 43.20% with international support by 2030. One of the main strategies in achieving this target is through ecosystem restoration, particularly forests and peatlands, which play a crucial role in carbon sequestration. However, restoration efforts still face challenges such as limited field data, delays in detecting ecosystem changes, and minimal technology integration in monitoring. To address these issues, this study proposes the use of an Internet of Things (IoT)-based monitoring system and smart sensors as an innovative solution. The research method used was a Literature Review, a research approach based on the collection, evaluation, and synthesis of various relevant scientific works to build a conceptual understanding of a topic. The results indicated that IoT implementation in Indonesia faces significant challenges, with network infrastructure in remote areas, limited implementation costs, uneven technical skills, and data security issues being the main obstacles. Furthermore, successful implementation requires institutional support, regulations, and local community participation to optimize the use of IoT-based monitoring systems.